A new method to detect Lonsdalea quercina in infected plant tissues by real‐time PCR. Issue 1 (5th June 2014) - Shang, J.; Liu, B. L.; He, W.; Belbahri, L.
Summary Presymptomatic and accurate diagnoses of pathogens are essential for disease prediction and the timely application of bactericide. The bacterium Lonsdalea quercina (=Brenneria quercina) has been reported as the causal agent of drippy nut and bark canker disease on oak in California (US) and Europe. In recent years, it is also found on Populus × euramericana trees in Henan province of China. This bacterium causes longitudinal cankers of a few centimetres in size on the bark surface of the upper trunk. In this study, we developed two species‐specific PCR assays using primer pairs LqfF/LqfR and LqgF/LqgR for the rapid and accurate detection of the pathogenic bacteria in diseased plant tissues. The results show that the LqfF/LqfR primers amplified only a single PCR band of approximately 382 bp and the LqgF/LqgR primers yielded a PCR product of approximately 286 bp. The two primers were successfully adapted to real‐time PCR based on SYBR Green I used with the ABI 7500 system. The detection limit of the reaction was 0.1 pg genomic DNA per 20 μl PCR reaction volumes. The pathogen was mainly detected in the phloem of cankers as well as in the exudates of diseased trees, but was not found in the xylem or leaves. The size of pathogen in distribution was larger than the lesion. The results demonstrate that real‐time PCR assays can be used to detect the pathogen by extracting DNA directly from infected plant tissues. This method is a rapid, reliable method for the presymptomatic and accurate detection of L. quercina, providing a useful insight into epidemiological studies.